Determination of Proposed Road on Rural Reserved Plot Using UAV at Parit Raja - Mohd Zukifli, Isma Haziq; Saifullizan bin Mohd Bukari (Recent Trends in Civil Engineering and Built Environment, 2023)
Road will be constructed as well as population growth roads are increasingly needed to identify areas for the purpose of proposed line in road reserve and road profile works, UAV is needed for mapping purpose to survey the proposed area of ​​new alignment access road. This is because there is a line of road reserve that needs to be upgraded. UAV platform are these days a significant source of information for review, observation, mapping and 3D representative issues. The purpose of this study is to observe road reserve, to plot a topography orthophoto map and analyze plot position road reserve in area Parit Raja using DJI Phantom 4 drone. This study provides the image acquisition, quality control and data processing of the road reserve at area and create outline three-dimensional mapping of topography using software analysis. A software application is being used to make 3D topography images and a map of the reserve road in Kg Parit Bengkok and Kg Parit Haji Salleh Ros, Johor in Malaysia. There are 80 data images made with a camera FC6310 (8.8mm) that cover the area’s road reserve topography through Agisoft Metashape and AutoCAD. As a result, a resolution accuracy of 1.77cm/pix 3D topography for road reserve modeling has been achieved. Photogrammetric applications, mapping, plot position and 3D displays can all be done with the DJI Phantom 4 drone for the whole process of this study.